Gabapentin dose and the 30-day risk of altered mental status in older adults: A retrospective population-based study - Fleet, Jamie L.; Dixon, Stephanie N.; Kuwornu, Paul John; Dev, Varun K.; Montero-Odasso, Manuel; Burneo, Jorge; Garg, Amit X. (PLOS ONE, 2018)
Gabapentin is an effective treatment for chronic neuropathic pain but may cause dizziness, drowsiness, and confusion in some older adults. The goal of this study was to assess the association between gabapentin dosing and adverse outcomes by obtaining estimates of the 30-day risk of hospitalization with altered mental status and mortality in older adults (mean age 76 years) in Ontario, Canada initiated on high dose (>600 mg/day; n = 34,159) compared to low dose (≤600 mg/day; n = 76,025) oral gabapentin in routine outpatient care. A population-based, retrospective cohort study assessing new gabapentin use between 2002 to 2014 was conducted. The primary outcome was 30-day hospitalization with an urgent head computed tomography (CT) scan in the absence of evidence of stroke (a proxy for altered mental status). The secondary outcome was 30-day all-cause mortality. The baseline characteristics measured in the two dose groups were similar. Initiation of a high versus low dose of gabapentin was associated with a higher risk of hospitalization with head CT scan (1.27% vs. 1.06%, absolute risk difference 0.21%, adjusted relative risk 1.29 [95% CI 1.14 to 1.46], number needed to treat 477) but not a statistically significant higher risk of mortality (1.25% vs. 1.16%, absolute risk difference of 0.09%, adjusted relative risk of 1.01 [95% CI 0.89 to 1.14]). Overall, the risk of being hospitalized with altered mental status after initiating gabapentin remains low, but may be reduced through the judicious use of gabapentin, use of the lowest dose to control pain, and vigilance for early signs of altered mental status.